2018
DOI: 10.22616/erdev2018.17.n184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of use of biogas plant digestate as fertilizer in alfalfa and winter wheat

Abstract: Abstract. Anaerobic decomposition of plant residues from which biogas is produced, generates very large amounts of digestate. Due to its physicochemical properties post-digestion liquid can be used as a fertilizer. Postdigestion liquid was used in the field cultivation of fodder alfalfa and winter wheat. The content of macroelements and the content of protein in the grains of winter wheat fertilized with digestate were on the same levels as in the grains of wheat fertilized with mineral fertilizers. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The obtained values were 0.119, 0.12 and 5.37 g•dm −1 for nitrogen, phosphorous and potassium, respectively ( Table 1). The content of heavy metals was within the acceptable range, which confirms the usability of the digestate as a crop fertilizer [39,40]. It is also important to note that the elemental analysis of the digestate was comparable to results reported by other authors [41].…”
Section: Resultssupporting
confidence: 85%
“…The obtained values were 0.119, 0.12 and 5.37 g•dm −1 for nitrogen, phosphorous and potassium, respectively ( Table 1). The content of heavy metals was within the acceptable range, which confirms the usability of the digestate as a crop fertilizer [39,40]. It is also important to note that the elemental analysis of the digestate was comparable to results reported by other authors [41].…”
Section: Resultssupporting
confidence: 85%
“…Moreover, the digestate contains substantial amounts of macroelements, therefore it can be used as a fertilizer. This is confirmed by the investigation conducted last year (Koszel et al 2016).…”
Section: Resultssupporting
confidence: 79%
“…This product, resulted from the digestion process contains more inorganic nitrogen than non-digested organic fertilizers, and, in consequence, more nitrogen in a form available for plants [88]. Previous studies conducted in EU countries demonstrated the possibility of using the digestate as a replacement for the traditional fertilizer or soil amendment, with the benefits both for the farmers (impact on the crop yields) and soil properties [89][90][91][92][93]. Nevertheless, in some cases the digestate management can be problematic for the biogas producers.…”
Section: Limitation For Development Of Agricultural Biogas Plants In mentioning
confidence: 99%